Aplikasi Augmented Reality Pengenalan Hewan Berdasarkan Jenis Pangan Berbasis Android - Adyan Wahyu Pratama; Sutarman; Saucha Diwandari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Augmented Reality applications have become one of the technologies that has developed rapidly in the last few decades. This technology will later be used to help solve challenges in the education sector. Common problems that occur in the world of education usually lie in learning methods. Teachers usually only use classical teaching aids and do not provide opportunities for students to explore further with existing media. Therefore, an Augmented Reality based application is used. Augmented Reality is a technology that combines digital information such as images, videos or 3D models with the user's environment in real time. Application design as Android-based learning media. This Augmented Reality application will later help students' learning process. The application runs on Android-based smartphones. The contents of this application will be a 3D model, detailed information about the animal. As well as audio that will explain the details of the animal. It is hoped that this application can facilitate students to learn about animals, especially based on types of food. In order to determine the effectiveness of the application being developed, a pretest and posttest were carried out. The results show that at the posttest students had better abilities compared to before